Green Synthesis of Silver Nanoparticles as Saturable Absorber for Q-switched Fiber Laser: Green Synthesis of Silver Nanoparticles - Mohd Abd Jalil, Nur Aina Aqilah (Enhanced Knowledge in Sciences and Technology, 2024)
We achieved Q-switching successfully inside an erbium-doped fiber laser (EDFL) cavity. The AgNPs was fabricated by using green synthesis approach by mixing green tea extract and AgNO3 solution. To form the AgNPs thin film as SA, the mixing solution was mixed with PVA solution. Operating at a maximum pump power of 190.30 mW, the Q-switched EDF achieved a minimum pulse width of 2.00 us and a maximum pulse energy of 0.20 nJ. As the repetition rate increases from 23.16 kHz to 56.93 kHz, the modulation depth was found to be 24.37%. This innovative work is important as a PVA-based SA based on AgNPs has been used to generate a Q-switched laser in the 1.00 um range. Our results present promising avenues for further development of Q-switched fiber laser technology. The findings help to develop sustainable nanotechnologies with practical applications in laser technology, paving the way for cleaner and more efficient devices in a variety of industrial and scientific domains